Testosterone abrogates TLR4 activation in prostate smooth muscle cells contributing to the preservation of a differentiated Phenotype - Leimgruber, Carolina (2013)
Prostate smooth muscle cells (pSMCs) are capable of responding to inflammatory stimuli by secreting proinflammatory products, which causes pSMCs to undergo dedifferentiation. Although it has been proposed that androgens decrease proinflammatory molecules in many cells and under various conditions, the role of testosterone in the prostate inflammatory microenvironment is still unclear. Therefore, our aim was to evaluate if testosterone was able to modulate the pSMCs response to bacterial LPS by stimulating primary pSMC cultures, containing testosterone or vehicle, with LPS (1 or 10mg/ml) for 24–48 h. The LPS challenge induced pSMCs dedifferentiation as evidenced by a decrease of calponin and alpha smooth muscle actin along with an increase of vimentin in a dose-dependent manner, whereas testosterone abrogated these alterations. Additionally, an ultrastructural analysis showed that pSMCs acquired a secretory profile after LPS and developed proteinopoietic organelles, while pSMCs preincubated with testosterone maintained a more differentiated phenotype. Testosterone downregulated the expression of surface TLR4 in control cells and inhibited any increase after LPS treatment. Moreover, testosterone prevented IkB-a degradation and the LPS-induced NF-kB nuclear translocation. Testosterone also decreased TNF-a and IL6 production by pSMCs after LPS as quantified by ELISA. Finally, we observed that testosterone inhibited the induction of pSMCs proliferation incited by LPS. Taken together, these results indicate that testosterone reduced the proinflammatory pSMCs response to LPS, with these cells being less reactive in the presence of androgens. In this context, testosterone might have a homeostatic role by contributing to preserve a contractile phenotype on pSMCs under inflammatory conditions.